(untitled) (Neo Scientific Peer Reviewed Journal, 2024)
Michael Morpurgo is an English writer known for his works for children in which animals play a central role. This article studies the animalistic genre in the works of this writer, his usage of animals as metaphors and symbols reflecting important social and humanistic themes. It analyses how animal images in Morpurgo’s works serve as a tool to convey moral lessons, empathy and understanding of human values, as well as the influence of the surrounding world on the fate of living beings.